Features of dimentional design system for asphalt concrete mix on superpave technology and bituminous binder of pg grade determination - N. I. Bryzgalov; A. F. Kemalov (Вестник СибАДИ, 2023)
Introduction. This article discusses the technology of designing asphalt concrete pavements, using the Superpave method. The Superpave (SUperior PERforming Asphalt PAVEments) system was developed by the Strategic Highway Research Program (SHRP) in the USA. The aim of the program was to find new ways of designing asphalt concrete pavements that will work better at extreme temperatures and heavy traffic loads.Currently, the system of volumetric design of asphalt concrete mixtures is being actively implemented in Russian road construction industry. This is an adaptation of the American Superpave method and is being implemented in our country in the form of a series of new standards. The Superpave volumetric and functional design system in particular addresses several pavement-related problems: permanent deformation, which results from poor asphalt mix shear strength at high temperatures, and low temperature damage, which occurs when the asphalt pavement is subjected to stress exceeding the compressive and tensile strength. The elimination of the above problems is carried out due to the most reasonable selection of the components of the asphalt concrete mixture.Materials and methods. Studies of bitumen binders were carried out according to the methods laid down in the technical requirements: GOST R 58400.1-2019 Public roads. Materials binding petroleum bitumen. Technical requirements taking into account the temperature ranges of operation.The selection of the PG brand of bitumen binder using Superpave technology was carried out using the example of a polymer-bitumen binder that meets the requirements of GOST 52056-2003 PBB 90 (sample 4) and a bitumen binder obtained from tar with the addition of thermoplastic elastomer (hereinafter referred to as TEP) of the SBS type that meets the requirements of GOST 52056-2003 PBB 90 (sample 3).Results. The article provides a review of technical documentation in order to familiarize with the methodology for selecting the brand of bituminous binder for asphalt mix. In the course of the research, the technological features of the system of volumetric functional design of the asphalt concrete mixture according to the Superpave method, as well as the determination of the brand of bituminous binder, were considered. The introduction of foreign experience in road construction can contribute to the improvement and improvement of the quality of Russian roads.Discussion and conclusions. Based on the experimental data carried out in the work, it can be concluded that the goal has been achieved, namely, the brands of bitumen binder have been selected using Superpave technology that meet the requirements of GOST R 58400.1–2019 and GOST R 58400.2-2019, namely for polymer-bitumen binder (PBB 90 according to GOST 52056-2003) – PG 58-28, and on the basis of tar with the addition of SBS – PG 64-28 grade TEP, respectively.Having studied the physical and chemical characteristics of the initial reagents, as well as the results of numerous chemical experiments, brands of PG bitumen binders were selected using Superpave technology and depending on climatic conditions and transport loads GOST R 58400.1-2019 Public roads. Materials binding petroleum bitumen. Technical requirements taking into account the temperature ranges of operation and GOST R 58400.22019 Public roads. Materials binding petroleum bitumen. Technical requirements taking into account the levels of operational transport loads.